PBL triggers in relation to students’ generated learning issues and predetermined faculty objectives: Study in a Malaysian public university - Ruslai, Nurulhidayati; Salam, Abdus (Professional Medical Publications, 2016)
Objectives: Foundational elements of problem based learning (PBL) are triggers, tutors and students. Ineffective triggers are important issues for students’ inability to generate appropriate learning issues. The objective of this study was to evaluate PBL triggers and to determine similarities of students’ generated learning issues with predetermined faculty objectives. Methods: It was a retrospective study conducted in 2014 analyzing all 24 PBL-triggers used at Centre for Foundation Studies, International Islamic University Malaysia, in four semesters during two consecutive years 2011 and 2012. Triggers were used as textual and illustration format equally in each semester. Total 16 PBL-triggers with highest and lowest achieving similarities of learning issues with predetermined faculty objectives were selected equally from each semester and format. The trigger quality and learning issues related to predetermine faculty objectives were analyzed and presented as mean and percent distribution. Results: Mean similarities score of students’ generated learning issues were 3.4 over 5 predetermined faculty objectives which was 68%, varied from 58% to 79%. More than 70% similarities were generated from five textual and four illustrated triggers, while <70% similarities observed from four illustrated and three textual triggers. Conclusion: Whatever the trigger formats in PBL, it is the designing considering influential variables that influence higher outcomes. Triggers should have planned clues that lead students to generate issues correlate with faculty objectives. Educational institution should emphasize on training needs of faculty at regular interval to develop and re-in force teachers’ skills in trigger design, thereby to promote a sustainable educational and organizational development.